P09.03 Array-CGH analysis in meningiomas adds further information of biological behavior. (6th September 2019) - Calatozzolo, C; Rizzo, A; Girgenti, V; Saladino, A; Patanè, M; Di Meco, F; Pollo, B; Sciacca, F L
Abstract: BACKGROUND: Meningioma is the most common primary tumor of CNS, usually a benign tumor (grade I) successfully treated by surgical resection, while in the 25–30% of cases is a more aggressive neoplasm with high recurrence rate and poor prognosis (grade II-III). In the last years some studies tried to investigate the genomic profile of meningioma to find additional prognostic factors and potential therapeutic targets. Aim of our study was to use the array-CGH (aCGH) to investigate possible indicators of recurrence risk in meningiomas. MATERIAL AND METHODS: We retrospectively selected two group of patients: 34 with meningioma WHO grade I (24 F, 10 M, median age at diagnosis 56 yrs) and 19 with meningioma WHO grade II (9 F, 10 M, median age 59 yrs), in order to compare cases recurrent and non-recurrent in each group. We also analyzed 5/18 recurrences WHO grade I and 10/11 WHO grade II. Genomic profiles were investigated by aCGH. RESULTS: We observed an increase in number of genomic imbalances related to grading and in non-recurrent versus recurrent tumors. 9 WHO I meningiomas were without alterations. The mainly alterations observed were deletions and duplications, moreover we also identified chromothripsis of a single chromosome in 2/18 WHO I recurrent and 2/8 WHO II non recurrent meningiomas, and chromothripsis of multiple chromosomes in 5/11 WHO II recurrent meningiomas. As well we detected the presence of mosaicism, mainly in WHO I recurrent and in grade II meningiomas. In 7/14 WHO I meningiomas we found differences in genomic profile analyzing two samples obtained from two distinct areas. 6/15 recurrences showed the same alterations of the primary tumor. We didn't detected an association between alteration of 1p and 22q and recurrence risk, as previously suggested, as those were the most diffused imbalances in all meningiomas. CONCLUSION: In our patients we found a difference in genomic imbalances between grade I and grade II meningiomas, but we also identified additional details of the complexity of alterations in meningioma with the detection of chromothripsis and mosaicism. This latter aspect is a new issue and suggests the presence of more aggressive cell clones that could be predictive of recurrence in grade I meningioma. Moreover, we observed a spatial heterogeneity in half of grade I meningioma analyzed. Our preliminary results suggest that the aCGH, a technique routinely used in many laboratories, could be used to better stratify meningioma patients.